A meta-analysis of cohort and pilot studies indicates association of mouthwash use and risk of hypertension in adults - Hala Abubaker Bagabir; Rgad Bagabir; Ayman K. Johargy; Hani Faidah; Ahmad O. Babalghith; Farkad Bantun; Faraz Ahmad; Darin Mansor Mathkor; Shafiul Haque (Journal of King Saud University: Science, 2024)
The relationship between high blood pressure (hypertension) incidence and mouthwash use is a subject of ongoing research. Origin of this link may lie in mouthwash-mediated destruction of oral microflora, and consequently reduced nitric oxide (NO) bioavailability. In this study, we evaluated the association between mouthwash use and the risk of hypertension through statistical meta-analysis of published cohort and cross-sectional studies. The search strategy and selection of research articles was in accord with PRISMA guidelines, and under pre-defined set of inclusion criteria. Primary research studies focused on “association among use of mouthwash and risk of hypertension incidence” were searched on databases such as PubMed, EMBASE, MEDLINE, and Cochrane Library. MesH keywords such as “hypertension”, “mouthwash use”, “risk of HTN”, “HTN incidence”, “nitric oxide bioavailability”, and “cohort studies” were used. Out of 1650 studies, 9 met all the inclusion criteria and were finally selected. RevMan 5.3 software was employed for statistical analyses of data retrieved from these selected studies. About 6384 adults with mild hypertension symptoms were included in this meta-analysis from different cohort, pilot and cross-sectional studies. All participants’ ages ranged between 40 and 60 years with mild symptoms of hypertension. While high statistical heterogeneity was observed, our results indicate a significant association of antiseptic mouthwash use with the risk of developing hypertension. The findings reveal a slightly but significantly elevated risk of development of hypertension among regular antiseptic mouthwash users, in comparison to non-users. However, further studies are needed to confirm and establish this relationship further.